Avaliação da fertilidade do solo e balanço nutricional das em áreas culturas de soja e trigo em áreas com agricultura de precisão na região oeste do Paraná - Rampim, Leandro (2014)
There is a growing use of the division of soil sampling in grids to make the recommendation to lime and fertilizer into a system of precision agriculture in western Paraná, disregarding the presence of terraces, essential for soil conservation.Thus, this study, funded by the Araucaria Foundation under agreement with Unioeste (Project 217/2012), aimed: (i) evaluate the spatial variability on the terraces; (ii) define and evaluate the variability of chemical attributes in management units; (iii) evaluation of nutritional balance using the diagnosis and recommendation integrated system (DRIS) in units of management in soybean; (iv) determine DRIS norms and appropriate range for the wheat crop; (v) validate the recommendation for phosphorus and potassium fertilization, by modeling the recommendation of lime and fertilizer to the soybean crop (SIRSo) and Table of fertilizer recommendation for soybean grown in Oxisol system. The studies were conducted in areas of cultivation in Guaira/PR, with the the delimitation of areas with Garmin GPS 12, and subsequently georeferenced from two precise points collected GPSs GTR-GII - L1/L2 - Geo Tech in each area, which were corrected with information from Brazilian Institute of Geography and Statistics (IBGE). Was conducted the assessment of soil chemical properties, foliar concentrations of macro and micronutrients except boron, nutritional balance with DRIS, number of plants and productivity.The experiments were performed during the cultivation of soybean crops in 2010/11, 2011/12 and 2012/13 and in the cultivation of wheat in the 2011 season. At the end of the work has been concluded: (i) the sections of the terraces have variability of soil chemical properties, but without interfering in foliar nutrient concentrations and nutrient balance in soybean; (ii) the implementation of precision farming system in western Paraná should be performed with the division of areas in management units, paying attention to the slope, historic area, cropping system, good sense of agronomist and especially the terraces; (iii) in soybean culture can be used for grouping methodology foliar concentrations in soybean in precision agriculture system in conjunction with the assessment of nutritional balance through DRIS, allowing to identify nutritional problems; (iv) in wheat culture, DRIS norms obtained, allows to interpret the nutritional status with adequate range of nutrients in other properties in the region; (v) fertilizer applied in the area of suitable soil chemical attributes, with the Tables of recommendation of the Embrapa or by modeling SIRSo levels do not increase the productivity of soybean, it is possible to omit the phosphate and potassium fertilization, following guidelines of Embrapa